2022
DOI: 10.1073/pnas.2113313119
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of brain-wide resting-state and functional somatosensory circuits by fMRI with optogenetic silencing

Abstract: To further advance functional MRI (fMRI)–based brain science, it is critical to dissect fMRI activity at the circuit level. To achieve this goal, we combined brain-wide fMRI with neuronal silencing in well-defined regions. Since focal inactivation suppresses excitatory output to downstream pathways, intact input and suppressed output circuits can be separated. Highly specific cerebral blood volume–weighted fMRI was performed with optogenetic stimulation of local GABAergic neurons in mouse somatosensory regions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 78 publications
(135 reference statements)
3
25
0
Order By: Relevance
“…S5 , details in Methods), the DMN is presented in Fig.4d , including prelimbic cortex, cingulate cortex, auditory cortex, posterior parietal cortex, and retrosplenial cortex. These results provide strong evidence for highly reliable detection of BOLD fMRI signals under experimental conditions, which are highly consistent with reports from other researchers [37-42].…”
Section: Resultssupporting
confidence: 92%
“…S5 , details in Methods), the DMN is presented in Fig.4d , including prelimbic cortex, cingulate cortex, auditory cortex, posterior parietal cortex, and retrosplenial cortex. These results provide strong evidence for highly reliable detection of BOLD fMRI signals under experimental conditions, which are highly consistent with reports from other researchers [37-42].…”
Section: Resultssupporting
confidence: 92%
“…Additionally, this framework provides little motivation for studying the impacts of top-down regions on pre-stimulus activity. However, we casually demonstrated that wMC robustly modulates S1 before stimulus onset in both anesthetized and awake behaving animals (see also Jung et al, 2022). Importantly, this pre-stimulus modulation is context-dependent, with a stronger drive onto putative inhibitory neurons in distractor-aligned S1.…”
Section: Discussionmentioning
confidence: 80%
“…Additionally, S1 receives top-down inputs from ipsilateral frontal cortex, most robustly from the whisker region of motor cortex (wMC). Stimulation and suppression studies have demonstrated robust yet varied impacts of wMC activity on S1, including through excitation (Jung et al, 2022; Lee et al, 2008; Manita et al, 2015; Petreanu et al, 2012; Rocco & Brumberg, 2007; Xu et al, 2012; Zagha et al, 2013), inhibition (Kinnischtzke et al, 2014; Zagha et al, 2016), and dis-inhibition (Lee et al, 2013). The impacts of wMC on S1 in the context of distractor suppression is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional FC measured by fMRI relies on covaried hemodynamic modulations at a resting state (RS). However, the underlying sources of RS FC are unclear and do not faithfully reflect neuronal RS circuits in mice 47 . Thus, we adopted EC measurements by directly modulating neuronal activities in source regions and reading out corresponding responses in the entire brain by fMRI.…”
Section: Discussionmentioning
confidence: 99%